Nucellain, a Barley Homolog of the Dicot Vacuolar-Processing Protease, Is Localized in Nucellar Cell Walls - Linnestad, Casper (American Society of Plant Physiologists, 1998)
The nucellus is a complex maternal grain tissue that embeds and feeds the developing cereal endosperm and embryo. Differential screening of a barley (Hordeum vulgare) cDNA library from 5-d-old ovaries resulted in the isolation of two cDNA clones encoding nucellus-specific homologs of the vacuolar-processing enzyme of castor bean (Ricinus communis). Based on the sequence of these barley clones, which are called nucellains, a homolog from developing corn (Zea mays) grains was also identified. In dicots the vacuolar-processing enzyme is believed to be involved in the processing of vacuolar storage proteins. RNA-blot and in situ-hybridization analyses detected nucellain transcripts in autolysing nucellus parenchyma cells, in the nucellar projection, and in the nucellar epidermis. No nucellain transcripts were detected in the highly vacuolate endosperm or in the other maternal tissues of developing grains such as the testa or the pericarp. Using an antibody raised against castor bean vacuolar-processing protease, a single polypeptide was recognized in protein extracts from barley grains. Immunogold-labeling experiments with this antibody localized the nucellain epitope not in the vacuoles, but in the cell walls of all nucellar cell types. We propose that nucellain plays a role in processing and/or turnover of cell wall proteins in developing cereal grains.